An Optimized Approach for Time-Constrained and Reliable Bursty Data Acquisition in WMSNs. (28th June 2015) - Vinh, Phan Van; Oh, Hoon
In real-time multimedia application that is used to monitor the safety of workers and working environment in industrial fields, a burst of multimedia data, such as still images and audio or video streams, generated by multimedia nodes equipped with cameras or microphones on demand, is required to be collected at a server within a specified time bound in a reliable manner. However, due to the limited resources in sensor devices, such as process capability, bandwidth, and energy, it is challengeable to satisfy the time constraints of various real-time multimedia applications. Therefore, we introduce an optimized approach in order to shorten the acquisition period of bursty traffic so that it can satisfy more applications with tighter time constraints. For this purpose, we devise a path reservation scheme for an energy-efficient and time-constrained data transmission and a frame-slot scheduling scheme using two channels that enables the concurrent data transmission. Simulation results show that our proposed approach reduces the bursty data acquisition time and enhances network throughput significantly compared to other ones.